A Senhora do Álbum de Família no mar que afoga a Casa e não devolve os corpos: a sociologização do texto teatral como método de leitura a partir de Garcia Lorca La Casa de Bernarda Alba e Nelson Rodrigues Álbum de Família e Senhora dos Afogados - Silva, Leonardo âmaro Nolasco (2008)
In the scenarios proposed by Garcia Lorca and Nelson Rodrigues, through the lives created by these dramatists in the shape of characters and storylines, it was tried in this thesis to reflect about a methodological path to read theatrical texts. Supported by the concept of "open work", credited to Umberto Eco, and by the "wood methaphor" proposed by the same author, it was appealed to the Sociology classics Marx, Durkheim and Weber and suggested reading maps based on their theoretic contributions. As a product of this "office ethnography", it is presented the method of "sociolization" of the theatrical scene, aiming to contribute to directors, authors and other drama readers with a new look on the scene being it the stage or the real life.